X-ray micro-CT measurement of large parts at very low temperature - Koutecký, T; Zikmund, T; Glittová, D; Paloušek, D; Živčák, J; Kaiser, J (The Review of scientific instruments, 2017)
At present, the automotive industry, along with other industries, has increasing demands on accuracy of produced parts and assemblies. Besides the regular dimensional and geometrical inspection, in some cases, also a verification at very low temperatures is required. X-ray computed tomography (CT), as a tool for non-destructive testing, is able to examine samples and then determine dimensions for strictly stable temperature conditions necessary for the stability of the CT system. Until now, no system that allows scanning of samples larger than a few millimeters at temperatures much below 0 °C has been presented. This paper presents a cooling system for CT imaging of parts with length up to 300 mm at the extreme temperature conditions of -40 °C, which are based on automotive industry requests. It describes the equipment and conditions under which it is possible to achieve a temperature stability of samples at low temperatures, while keeping an independent temperature regulation of the CT system. The presented system uses a standard industrial CT device and a newly designed cooling stage with passive cooling based on phase-change material. The system is demonstrated on the measurement of plastic part (car door handle) at temperatures of -40 °C and 20 °C. The paper also presents the method of how to interpret the thermal changes using tools of the commercial software VGStudio MAX (Volume Graphics GmbH, Germany).